Photochromic polyester fiber and preparation method thereof
By grafting modification and coating treatment of PET fibers, tungsten trioxide nanoparticles were prepared in combination with hydrothermal method, and ethylenediaminetetraacetic acid was used as a chelating agent, the problem of polyester fiber's color change function not continuous and the coating was easily peeled off, achieving an efficient and durable photochromic change effect.
Patent Information
- Application Number
- CN202411972891.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-03-28
AI Technical Summary
The prior art is difficult to impart a long-term and effective color change function to polyester fibers through simple preparation processes, and there are problems such as easy coating to fall off and poor durability.
By grafting modification operations on PET fibers, a coating solution that can form a strong interface bonding with grafted polyester fibers was designed and prepared. Tungsten trioxide nanoparticles were prepared by hydrothermal method, and coating was performed on the polyester fibers. Ethylene diaminetetraacetic acid was used as a powerful metal ion chelating agent to improve the stability of the fiber.
While polyester fiber has good reversible color discoloration performance and light response speed, it solves the problems of easy coating falling off and poor durability, and significantly improves the stability and color retention time of the fiber under environmental conditions.
Smart Images

Figure CN119711180A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polyester fiber preparation, in particular to a photochromic polyester fiber and a preparation method thereof. Background Art
[0002] In recent years, the chemical fiber industry has expanded too fast, with serious overcapacity and a significant reduction in the profit margin of conventional products. As a result, the chemical fiber industry is in a stage of deep development, upgrading and transformation, and product functional differentiation has become an important development trend. Among the many functional fibers, smart color-changing fibers have become a research hotspot because they are widely used in potential fields such as wearable devices and military camouflage. At present, smart color-changing fibers are divided into electrochromic fibers and photochromic fibers according to the color-changing principle. Compared with electrochromic fibers, photochromic fibers are more widely used in wearable devices and other fields due to their simple preparation process and color-changing principle.
[0003] In the prior art, the technical methods that can impart photochromic function to polyester fibers mainly include the following: for example, a polyamide / polyester photochromic composite fiber is recorded in the patent with patent announcement number CN105603576A. This scheme obtains photochromic fibers by blending the color-changing material with PET masterbatch and then melt-spinning. However, organic color-changing materials have poor thermal stability and oxidation resistance, low fatigue resistance and other problems, resulting in many difficulties in the preparation process of functionalized fibers and the obtained fibers; for example, the photochromic polyester, polyester fiber and preparation method recorded in the patent with patent announcement number CN115594855A. This scheme wraps the color-changing material in the masterbatch to protect the color-changing material, and then melt-spins the masterbatch and PET masterbatch to obtain photochromic polyester fibers. However, the color-changing masterbatch The modification process during preparation is relatively cumbersome, and the ratio of the secondary color masterbatch to the PET masterbatch during melt spinning cannot be strictly controlled. Adding too much or too little color masterbatch will cause problems such as unclear reversible color change or poor color matching effect. For example, the preparation method of photochromic fiber recorded in the patent announcement number CN118223287A, the scheme is to coat the PET polyester fiber, that is, to modify the fiber surface by using the nanosol produced by the sol-gel process, and to prepare the coating solution by mixing the inorganic metal oxide photochromic substance tungsten trioxide with polyvinyl alcohol, which can be theoretically applied to the functional modification of polyester fiber. However, since the PET fiber itself has a high degree of crystallinity, a smooth surface and hydrophobic properties, the interfacial bonding between the functional coating and the PET fiber is weak, and there are problems such as easy detachment of the coating and poor durability. Therefore, how to give the polyester fiber a long-lasting and effective color change function through a simple preparation process is a problem that needs to be solved at present, and there are still certain challenges.
[0004] Based on this, a photochromic polyester fiber and a preparation method thereof are now provided, which can eliminate the disadvantages of the prior art solutions. Summary of the invention
[0005] The object of the present invention is to provide a photochromic polyester fiber and a preparation method thereof, so as to solve the problem in the background art that it is impossible to give the polyester fiber a long-lasting and effective color-changing function through a simple preparation process.
[0006] To achieve the above object, the present invention provides the following technical solutions:
[0007] A method for preparing a photochromic polyester fiber comprises the following steps:
[0008] Step 1: Performing a grafting modification operation on a polyester fiber using a PET fiber sample to obtain an amino-grafted polyester fiber;
[0009] Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method;
[0010] Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution;
[0011] Step 4: soak the amino-grafted polyester fiber in the coating solution, and dry the soaked polyester fiber to obtain the photochromic polyester fiber.
[0012] Preferably, the grafting modification operation of the polyester fiber in step 1 specifically comprises the following steps:
[0013] Step 11: immersing the PET fiber in an ultrasonic tank containing an ethanol solution, cleaning the PET fiber using ultrasonic technology, drying the cleaned PET fiber with argon gas, and storing it in a desiccator at room temperature;
[0014] Step 12: placing the dried PET fiber sample into a spherical glass flask reactor, wherein the spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device;
[0015] Step 13: When the vacuum degree is increased to a specific value, ethylenediamine vapor is injected into the reactor to perform ionization operation, and the above process is repeated several times;
[0016] Step 14: washing the treated fiber with ultrapure water, drying with argon gas and storing after washing three times to obtain amino-grafted polyester fiber;
[0017] Step 15: indirectly test the grafting effect of the amino-grafted polyester fiber by a water contact angle test method.
[0018] Preferably, the input power of the plasma in step 12 is 150-200 W, and the treatment time of the plasma is 5-15 min.
[0019] Preferably, the vacuum degree in step 13 is 1 to 1.5×10 -1 mbar, and the steam flow rate is 70-80sccm.
[0020] Preferably, the step 2 of preparing tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate specifically comprises the following steps:
[0021] Step 21: dissolving sodium tungstate and sodium sulfate in distilled water, adding HCl solution dropwise to the solution while stirring, and adjusting the solution to a specific pH after stirring for a period of time, wherein the weight ratio of sodium tungstate and sodium sulfate is 2.5-5:3-6;
[0022] Step 22: transferring the mixture solution to a stainless steel autoclave lined with polytetrafluoroethylene, and generating a new product by a hydrothermal reaction;
[0023] Step 23: collect the new product by high-speed centrifugation, wash the product with distilled water and ethanol to a neutral solution, dry the neutral solution at 60°C to obtain tungsten trioxide nanoparticles, the average diameter of the tungsten trioxide nanoparticles is 70 to 200 nm.
[0024] Preferably, the reaction conditions of the hydrothermal method in step 22 are: keeping warm at 170-185° C. for 36-48 hours.
[0025] Preferably, the step 3 specifically comprises the following steps:
[0026] Step 31: dissolving the carboxyl-modified PEG in DMF, adding a cross-linking agent, and stirring the solution until the above substances are completely dissolved in the solution to obtain a PEG solution with a concentration of 10 to 15%;
[0027] Step 32: Add tungsten trioxide nanoparticle powder to the above solution, then add a dispersant, mix for 6 hours, then add 0.3-0.6 mmol of ethylenediaminetetraacetic acid, stir again for 6-12 hours to obtain a coating solution.
[0028] Preferably, the cross-linking agents in step 31 are EDC and NHS, the concentration range of EDC is 500-800 mM, and the concentration range of NHS is 150-300 mM.
[0029] Preferably, the mass proportion of the tungsten trioxide nanoparticle powder in the coating solution in step 32 is 7-14%, the dispersant is set to fatty alcohol polyoxyethylene ether, and the amount of the fatty alcohol polyoxyethylene ether added is set to 0.5-1% of the total amount of the tungsten trioxide nanoparticle powder.
[0030] Preferably, step 4 specifically includes the following steps: soaking the amino-grafted polyester fiber in step 1 in the coating solution prepared in step 3, maintaining the temperature of the coating solution between 60 and 65°C, maintaining the pH value between 4 and 6 during the soaking process, and soaking time is 25 to 40 minutes, and then drying the polyester fiber after soaking to obtain photochromic polyester fiber.
[0031] Compared with the prior art, the present invention has the following beneficial effects:
[0032] The photochromic polyester fiber and preparation method thereof adopt a relatively simple process, starting from modifying the surface of the polyester fiber with a nanosol, and designing and preparing a coating solution capable of forming a strong interface adhesion with the grafted polyester fiber by grafting modification operations on the polyester fiber. The photochromic polyester fiber is then obtained by coating the coating solution, so that the fiber has good reversible color change performance and light response speed while solving the problems of easy shedding of the coating and poor durability. The fiber can be widely used in potential fields such as wearable devices. In addition, the method also uses ethylenediaminetetraacetic acid as a strong metal ion chelating agent, which is convenient for affecting the valence state and photoactive behavior of metal atoms, significantly improving the stability of the fiber under environmental conditions, and enabling the photochromic polyester fiber to achieve a longer color retention time, thus having good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1 It is a schematic diagram of the steps of the present invention. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.
[0035] Example 1
[0036] A photochromic polyester fiber and a preparation method thereof, such as Figure 1 As shown, the specific steps include:
[0037] Step 1: Performing a grafting modification operation on polyester fiber using a PET fiber sample to obtain amino-grafted polyester fiber;
[0038] Specifically, in this embodiment, a PET fiber material with a model of ZW120 and a specification of 1.56 dtex×51 mm was selected, and the PET fiber was immersed in an ultrasonic tank containing an ethanol solution, and the PET fiber was cleaned for 15 minutes using ultrasonic technology, and the cleaned PET fiber was dried with argon gas and stored in a desiccator at room temperature. The dried PET fiber sample was placed in a spherical glass flask reactor with a capacity of 500 mL. The spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device. When the vacuum degree is increased to 1×10 -1 mbar, open the valve containing ethylenediamine vapor, i.e., EDA, and inject ethylenediamine vapor into the reactor to perform ionization operation. At this time, the steam flow rate is 70 sccm, and the plasma input power is 150 W. After 5 minutes of plasma treatment, the above process is repeated 3 times, and the treated fiber is washed with ultrapure water. After washing three times, it is dried with argon and stored to obtain amino-grafted polyester fiber. The grafting effect of the amino-grafted polyester fiber is indirectly tested by a water contact angle test method. The contact angle of the amino-grafted polyester fiber is 45°.
[0039] Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method;
[0040] Specifically, the weight ratio between sodium tungstate and sodium sulfate in this embodiment is 2.5:3. 2.5g sodium tungstate and 3.0g sodium sulfate are dissolved in 100mL distilled water. A 2.5mol / L HCl solution is added dropwise to the solution while stirring to adjust the pH value of the solution to 1.5. After stirring for 10 minutes, the mixture solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and a new product is generated by a hydrothermal reaction. The reaction conditions at this time are to keep warm at 170°C for 40h. The new product is collected by centrifugation in a high-speed centrifuge. The speed of the centrifuge is 4000 rpm. The product is then washed with distilled water and ethanol to a neutral solution. The neutral solution is dried at a temperature of 60°C to obtain tungsten trioxide nanoparticles. The average diameter of the tungsten trioxide nanoparticles is 170nm.
[0041] Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution;
[0042] Specifically, the carboxyl-modified PEG, i.e., COOH-PEG-COOH, is dissolved in DMF, and the molecular weight at this time is 1000. 500 mm of EDC and 150 mm of NHS are added as cross-linking agents, and the pH value is adjusted to 4. The solution is stirred at 60° C. and 400 r / min until the above substances are completely dissolved in the solution to obtain a 10% concentration of PEG solution. Tungsten trioxide nanoparticle powder is added to the above solution, and the mass proportion of tungsten trioxide nanoparticle powder in the coating solution is 7%. Fatty alcohol polyoxyethylene ether is added as a dispersant, and the amount of fatty alcohol polyoxyethylene ether added is set to 0.5% of the total amount of tungsten trioxide nanoparticle powder. After mixing for 6 hours, 0.3 mmol of ethylenediaminetetraacetic acid is added, and stirred for 6 hours again to obtain a coating solution.
[0043] Step 4: soaking the amino-grafted polyester fiber in the coating solution, and drying the soaked polyester fiber to obtain a photochromic polyester fiber;
[0044] Specifically, the amino-grafted polyester fiber in step 1 is immersed in the coating solution prepared in step 3. The temperature of the coating solution during the immersion process is 60°C, the pH value is 4, and the immersion time is 25 minutes. The polyester fiber after the immersion is taken out and placed in an oven at 45°C for drying to obtain a photochromic polyester fiber.
[0045] Example 2
[0046] A photochromic polyester fiber and a preparation method thereof, such as Figure 1 As shown, the specific steps include:
[0047] Step 1: Performing a grafting modification operation on polyester fiber using a PET fiber sample to obtain amino-grafted polyester fiber;
[0048] Specifically, in this embodiment, a PET fiber material with a model of ZW121 and a specification of 1.56 dtex×65 mm was selected, and the PET fiber was immersed in an ultrasonic tank containing an ethanol solution, and the PET fiber was cleaned for 25 minutes using ultrasonic technology, and the cleaned PET fiber was dried with argon gas and stored in a dryer at room temperature. The dried PET fiber sample was placed in a spherical glass flask reactor with a capacity of 500 mL. The spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device. When the vacuum degree is increased to 1.5×10 -1mbar, open the valve containing ethylenediamine vapor, i.e., EDA, and inject ethylenediamine vapor into the reactor to perform ionization operation. At this time, the steam flow rate is 80 sccm, and the plasma input power is 200 W. After 15 minutes of plasma treatment, the above process is repeated 5 times, and the treated fiber is washed with ultrapure water. After washing three times, it is dried with argon and stored to obtain amino-grafted polyester fiber. The grafting effect of the amino-grafted polyester fiber is indirectly tested by a water contact angle test method. The contact angle of the amino-grafted polyester fiber is 29°.
[0049] Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method;
[0050] Specifically, the weight ratio between sodium tungstate and sodium sulfate in this embodiment is 5:6. 5g sodium tungstate and 6g sodium sulfate are dissolved in 150mL distilled water, and a 5mol / L HCl solution is added dropwise to the solution while stirring to adjust the pH value of the solution to 3. After stirring for 25 minutes, the mixture solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and a new product is generated by a hydrothermal reaction. The reaction conditions at this time are to keep warm at 185°C for 48 hours, and the new product is collected by centrifugation in a high-speed centrifuge. The speed of the centrifuge is 5000 revolutions per minute, and the product is washed with distilled water and ethanol to a neutral solution. The neutral solution is dried at a temperature of 60°C to obtain tungsten trioxide nanoparticles. The average diameter of the tungsten trioxide nanoparticles is 190nm.
[0051] Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution;
[0052] Specifically, the carboxyl-modified PEG, i.e., COOH-PEG-COOH, is dissolved in DMF, and the molecular weight at this time is 1500. 800 mm of EDC and 300 mm of NHS are added as cross-linking agents, and the pH value is adjusted to 6. The solution is stirred at 65° C. and 550 r / min until the above substances are completely dissolved in the solution to obtain a 15% concentration of PEG solution. Tungsten trioxide nanoparticle powder is added to the above solution, and the mass proportion of tungsten trioxide nanoparticle powder in the coating solution is 14%. Fatty alcohol polyoxyethylene ether is added as a dispersant, and the amount of fatty alcohol polyoxyethylene ether added is set to 1% of the total amount of tungsten trioxide nanoparticle powder. After mixing for 6 hours, 0.6 mmol of ethylenediaminetetraacetic acid is added, and the mixture is stirred for 12 hours again to obtain a coating solution.
[0053] Step 4: soaking the amino-grafted polyester fiber in the coating solution, and drying the soaked polyester fiber to obtain a photochromic polyester fiber;
[0054] Specifically, the amino-grafted polyester fiber in step 1 is immersed in the coating solution prepared in step 3. The temperature of the coating solution during the immersion process is 65°C, the pH value is 6, and the immersion time is 40 minutes. The polyester fiber after the immersion is taken out and placed in an oven at 60°C for drying to obtain a photochromic polyester fiber.
[0055] Example 3
[0056] A photochromic polyester fiber and a preparation method thereof, such as Figure 1 As shown, the specific steps include:
[0057] Step 1: Performing a grafting modification operation on polyester fiber using a PET fiber sample to obtain amino-grafted polyester fiber;
[0058] Specifically, in this embodiment, a PET fiber material with a model of ZW122 and a specification of 2.22 dtex×51 mm is selected, the PET fiber is immersed in an ultrasonic tank containing an ethanol solution, the PET fiber is cleaned for 20 minutes using ultrasonic technology, the cleaned PET fiber is dried with argon gas, and stored in a dryer at room temperature, and the dried PET fiber sample is placed in a spherical glass flask reactor with a capacity of 500 mL. The spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device. When the vacuum degree is increased to 1 mbar, After that, the valve containing ethylenediamine vapor, namely EDA, was opened, and the ethylenediamine vapor was injected into the reactor to perform ionization operation. At this time, the steam flow rate was 70-80 sccm, and the plasma input power was 170 W. After 10 minutes of plasma treatment, the above process was repeated 4 times, and the treated fiber was washed with ultrapure water. After washing three times, it was dried with argon and stored to obtain amino-grafted polyester fiber. The grafting effect of the amino-grafted polyester fiber was indirectly tested by a water contact angle test method. The contact angle of the amino-grafted polyester fiber was 36°.
[0059] Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method;
[0060] Specifically, the weight ratio between sodium tungstate and sodium sulfate in this embodiment is 3:4.2. 3g sodium tungstate and 4.2g sodium sulfate are dissolved in 120mL distilled water, and a 4mol / L HCl solution is added dropwise to the solution while stirring to adjust the pH value of the solution to 2. After stirring for 15 minutes, the mixture solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and a new product is generated by a hydrothermal reaction. The reaction conditions at this time are to keep warm at 180°C for 45h, and the new product is collected by centrifugation in a high-speed centrifuge. The speed of the centrifuge is 4500 rpm, and the product is washed with distilled water and ethanol to a neutral solution. The neutral solution is dried at a temperature of 60°C to obtain tungsten trioxide nanoparticles. The average diameter of the tungsten trioxide nanoparticles is 183nm.
[0061] Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution;
[0062] Specifically, the carboxyl-modified PEG, i.e., COOH-PEG-COOH, is dissolved in DMF, and the molecular weight at this time is 2000. 500-800 mm of EDC and 200 mm of NHS are added as cross-linking agents, and the pH value is adjusted to 4. The solution is stirred at 62° C. and 500 r / min until the above substances are completely dissolved in the solution to obtain a PEG solution with a concentration of 12%. Tungsten trioxide nanoparticle powder is added to the above solution, and the mass proportion of tungsten trioxide nanoparticle powder in the coating solution is 13%. Fatty alcohol polyoxyethylene ether is added as a dispersant, and the amount of fatty alcohol polyoxyethylene ether added is set to 0.8% of the total amount of tungsten trioxide nanoparticle powder. After mixing for 6 hours, 0.4 mmol of ethylenediaminetetraacetic acid is added, and the mixture is stirred for 10 hours again to obtain a coating solution.
[0063] Step 4: soaking the amino-grafted polyester fiber in the coating solution, and drying the soaked polyester fiber to obtain a photochromic polyester fiber;
[0064] Specifically, the amino-grafted polyester fiber in step 1 is immersed in the coating solution prepared in step 3. The temperature of the coating solution during the immersion process is 60°C, the pH value is 5, and the immersion time is 40 minutes. The polyester fiber after the immersion is taken out and placed in an oven at 60°C for drying to obtain a photochromic polyester fiber.
[0065] Example 4
[0066] A photochromic polyester fiber and a preparation method thereof, such as Figure 1 As shown, the specific steps include:
[0067] Step 1: Performing a grafting modification operation on polyester fiber using a PET fiber sample to obtain amino-grafted polyester fiber;
[0068] Specifically, in this embodiment, a PET fiber material with a model of ZW123 and a specification of 2.22 dtex×65 mm was selected, and the PET fiber was immersed in an ultrasonic tank containing an ethanol solution, and the PET fiber was cleaned for 22 minutes using ultrasonic technology, and the cleaned PET fiber was dried with argon gas and stored in a dryer at room temperature. The dried PET fiber sample was placed in a spherical glass flask reactor with a capacity of 500 mL. The spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device. When the vacuum degree is increased to 1.5×10 -1 mbar, open the valve containing ethylenediamine vapor, i.e., EDA, and inject ethylenediamine vapor into the reactor to perform ionization operation. At this time, the steam flow rate is 80 sccm, and the plasma input power is 200 W. After 15 minutes of plasma treatment, the above process is repeated 3 times, and the treated fiber is washed with ultrapure water. After washing three times, it is dried with argon and stored to obtain amino-grafted polyester fiber. The grafting effect of the amino-grafted polyester fiber is indirectly tested by a water contact angle test method. The contact angle of the amino-grafted polyester fiber is 30°.
[0069] Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method;
[0070] Specifically, the weight ratio between sodium tungstate and sodium sulfate in this embodiment is 4:4. 4g sodium tungstate and 4g sodium sulfate are dissolved in 110mL distilled water, and a 3mol / L HCl solution is added dropwise to the solution while stirring to adjust the pH value of the solution to 3. After stirring for 25 minutes, the mixture solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and a new product is generated by a hydrothermal reaction. The reaction conditions at this time are kept at 180°C for 48 hours, and the new product is collected by centrifugation in a high-speed centrifuge. The speed of the centrifuge is 5000 revolutions per minute, and the product is washed with distilled water and ethanol to a neutral solution. The neutral solution is dried at a temperature of 60°C to obtain tungsten trioxide nanoparticles. The average diameter of the tungsten trioxide nanoparticles is 178nm.
[0071] Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution;
[0072] Specifically, the carboxyl-modified PEG, i.e., COOH-PEG-COOH, is dissolved in DMF, and the molecular weight at this time is 1500. 600 mm EDC and 200 mm NHS are added as cross-linking agents, and the pH value is adjusted to 4. The solution is stirred at 65° C. and 500 r / min until the above substances are completely dissolved in the solution to obtain a PEG solution with a concentration of 12%. Tungsten trioxide nanoparticle powder is added to the above solution, and the mass proportion of tungsten trioxide nanoparticle powder in the coating solution is 14%. Fatty alcohol polyoxyethylene ether is added as a dispersant, and the amount of fatty alcohol polyoxyethylene ether added is set to 0.8% of the total amount of tungsten trioxide nanoparticle powder. After mixing for 6 hours, 0.5 mmol of ethylenediaminetetraacetic acid is added, and stirred for 6 hours again to obtain a coating solution.
[0073] Step 4: soaking the amino-grafted polyester fiber in the coating solution, and drying the soaked polyester fiber to obtain a photochromic polyester fiber;
[0074] Specifically, the amino-grafted polyester fiber in step 1 is immersed in the coating solution prepared in step 3. The temperature of the coating solution during the immersion process is 60°C, the pH value is 4, and the immersion time is 30 minutes. The polyester fiber after the immersion is taken out and placed in an oven at 50°C for drying to obtain a photochromic polyester fiber.
[0075] Example 5
[0076] A photochromic polyester fiber and a preparation method thereof, such as Figure 1 As shown, the specific steps include:
[0077] Step 1: Performing a grafting modification operation on polyester fiber using a PET fiber sample to obtain amino-grafted polyester fiber;
[0078] Specifically, in this embodiment, a PET fiber material with a model of ZW120 and a specification of 1.56 dtex×51 mm was selected, and the PET fiber was immersed in an ultrasonic tank containing an ethanol solution, and the PET fiber was cleaned for 15 minutes using ultrasonic technology, and the cleaned PET fiber was dried with argon gas and stored in a dryer at room temperature. The dried PET fiber sample was placed in a spherical glass flask reactor with a capacity of 500 mL. The spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device. When the vacuum degree is increased to 1.5×10 -1mbar, open the valve containing ethylenediamine vapor, namely EDA, and inject ethylenediamine vapor into the reactor to perform ionization operation. At this time, the steam flow rate is 70-80sccm, and the plasma input power is 200W. After 12 minutes of plasma treatment, the above process is repeated 3 times, and the treated fiber is washed with ultrapure water. After washing three times, it is dried with argon and stored to obtain amino-grafted polyester fiber. The grafting effect of the amino-grafted polyester fiber is indirectly tested by a water contact angle test method. The contact angle of the amino-grafted polyester fiber is 32°;
[0079] Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method;
[0080] Specifically, the weight ratio between sodium tungstate and sodium sulfate in this embodiment is 2.5:4. 2.5g sodium tungstate and 4g sodium sulfate are dissolved in 150mL distilled water, and a HCl solution with a concentration of 2.5-5mol / L is added dropwise to the solution while stirring to adjust the pH value of the solution to 3. After stirring for 15 minutes, the mixture solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and a new product is generated by a hydrothermal reaction. The reaction conditions at this time are kept at 170°C for 45h, and the new product is collected by centrifugation in a high-speed centrifuge. The speed of the centrifuge is 4000 rpm, and the product is washed with distilled water and ethanol to a neutral solution. The neutral solution is dried at a temperature of 60°C to obtain tungsten trioxide nanoparticles. The average diameter of the tungsten trioxide nanoparticles is 172nm.
[0081] Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution;
[0082] Specifically, the carboxyl-modified PEG, i.e., COOH-PEG-COOH, is dissolved in DMF, and the molecular weight at this time is 1000. 600 mm of EDC and 300 mm of NHS are added as cross-linking agents, and the pH value is adjusted to 4. The solution is stirred at 65° C. and 550 r / min until the above substances are completely dissolved in the solution to obtain a PEG solution with a concentration of 11%. Tungsten trioxide nanoparticle powder is added to the above solution, and the mass proportion of tungsten trioxide nanoparticle powder in the coating solution is 8%. Fatty alcohol polyoxyethylene ether is added as a dispersant, and the amount of fatty alcohol polyoxyethylene ether added is set to 1% of the total amount of tungsten trioxide nanoparticle powder. After mixing for 6 hours, 0.4 mmol of ethylenediaminetetraacetic acid is added, and the mixture is stirred for 10 hours again to obtain a coating solution.
[0083] Step 4: soaking the amino-grafted polyester fiber in the coating solution, and drying the soaked polyester fiber to obtain a photochromic polyester fiber;
[0084] Specifically, the amino-grafted polyester fiber in step 1 is immersed in the coating solution prepared in step 3. The temperature of the coating solution during the immersion process is 60°C, the pH value is 4, and the immersion time is 30 minutes. The polyester fiber after the immersion is taken out and placed in an oven at 55°C for drying to obtain a photochromic polyester fiber.
[0085] Example 6
[0086] A photochromic polyester fiber and a preparation method thereof, such as Figure 1 As shown, the specific steps include:
[0087] Step 1: Performing a grafting modification operation on polyester fiber using a PET fiber sample to obtain amino-grafted polyester fiber;
[0088] Specifically, in this embodiment, a PET fiber material with a model of ZW121 and a specification of 1.56 dtex×51 mm was selected, and the PET fiber was immersed in an ultrasonic tank containing an ethanol solution, and the PET fiber was cleaned for 20 minutes using ultrasonic technology, and the cleaned PET fiber was dried with argon gas and stored in a dryer at room temperature. The dried PET fiber sample was placed in a spherical glass flask reactor with a capacity of 500 mL. The spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device. When the vacuum degree is increased to 1.5×10 -1 mbar, open the valve containing ethylenediamine vapor, namely EDA, and inject ethylenediamine vapor into the reactor to perform ionization operation. At this time, the steam flow rate is 70-80sccm, and the plasma input power is 150W. After 15 minutes of plasma treatment, the above process is repeated 5 times, and the treated fiber is washed with ultrapure water. After washing three times, it is dried with argon and stored to obtain amino-grafted polyester fiber. The grafting effect of the amino-grafted polyester fiber is indirectly tested by a water contact angle test method. The contact angle of the amino-grafted polyester fiber is 33°;
[0089] Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method;
[0090] Specifically, the weight ratio between sodium tungstate and sodium sulfate in this embodiment is 3.5:5. 3.5g sodium tungstate and 5g sodium sulfate are dissolved in 150mL distilled water, and a 2.5mol / L HCl solution is added dropwise to the solution while stirring to adjust the pH value of the solution to 1.5. After stirring for 10 minutes, the mixture solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and a new product is generated by a hydrothermal reaction. The reaction conditions at this time are to keep warm at 185°C for 48h, and the new product is collected by centrifugation in a high-speed centrifuge. The speed of the centrifuge is 5000 rpm, and the product is washed with distilled water and ethanol to a neutral solution. The neutral solution is dried at a temperature of 60°C to obtain tungsten trioxide nanoparticles. The average diameter of the tungsten trioxide nanoparticles is 188nm.
[0091] Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution;
[0092] Specifically, the carboxyl-modified PEG, i.e., COOH-PEG-COOH, is dissolved in DMF, and the molecular weight at this time is 1000. 650 mm of EDC and 260 mm of NHS are added as cross-linking agents, and the pH value is adjusted to 4. The solution is stirred at 65° C. and 500 r / min until the above substances are completely dissolved in the solution to obtain a PEG solution with a concentration of 13%. Tungsten trioxide nanoparticle powder is added to the above solution, and the mass proportion of tungsten trioxide nanoparticle powder in the coating solution is 7%. Fatty alcohol polyoxyethylene ether is added as a dispersant, and the amount of fatty alcohol polyoxyethylene ether added is set to 0.9% of the total amount of tungsten trioxide nanoparticle powder. After mixing for 6 hours, 0.6 mmol of ethylenediaminetetraacetic acid is added, and the mixture is stirred for 12 hours again to obtain a coating solution.
[0093] Step 4: soaking the amino-grafted polyester fiber in the coating solution, and drying the soaked polyester fiber to obtain a photochromic polyester fiber;
[0094] Specifically, the amino-grafted polyester fiber in step 1 is immersed in the coating solution prepared in step 3. The temperature of the coating solution during the immersion process is 65°C, the pH value is 4, and the immersion time is 25 minutes. The polyester fiber after the immersion is taken out and placed in an oven at 60°C for drying to obtain a photochromic polyester fiber.
[0095] Example 7
[0096] A photochromic polyester fiber and a preparation method thereof, such as Figure 1 As shown, the specific steps include:
[0097] Step 1: Performing a grafting modification operation on polyester fiber using a PET fiber sample to obtain amino-grafted polyester fiber;
[0098] Specifically, in this embodiment, a PET fiber material with a model of ZW122 and a specification of 2.22 dtex×51 mm was selected, and the PET fiber was immersed in an ultrasonic tank containing an ethanol solution, and the PET fiber was cleaned for 20 minutes using ultrasonic technology, and the cleaned PET fiber was dried with argon gas and stored in a dryer at room temperature. The dried PET fiber sample was placed in a spherical glass flask reactor with a capacity of 500 mL. The spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device. When the vacuum degree is increased to 1.5×10 -1 mbar, open the valve containing ethylenediamine vapor, i.e., EDA, and inject ethylenediamine vapor into the reactor to perform ionization operation. At this time, the steam flow rate is 70 sccm, and the plasma input power is 180 W. After 10 minutes of plasma treatment, the above process is repeated 3 times, and the treated fiber is washed with ultrapure water. After washing three times, it is dried with argon and stored to obtain amino-grafted polyester fiber. The grafting effect of the amino-grafted polyester fiber is indirectly tested by a water contact angle test method. The contact angle of the amino-grafted polyester fiber is 37°.
[0099] Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method;
[0100] Specifically, the weight ratio between sodium tungstate and sodium sulfate in this embodiment is 3.5:4.5. 3.5g sodium tungstate and 4.5g sodium sulfate are dissolved in 120mL distilled water, and a HCl solution with a concentration of 2.5-5mol / L is added dropwise to the solution while stirring to adjust the pH value of the solution to 1.5. After stirring for 20 minutes, the mixture solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and a new product is generated by a hydrothermal reaction. The reaction conditions at this time are kept at 180°C for 42 hours, and the new product is collected by centrifugation in a high-speed centrifuge. The speed of the centrifuge is 4000 revolutions per minute, and the product is washed with distilled water and ethanol to a neutral solution. The neutral solution is dried at a temperature of 60°C to obtain tungsten trioxide nanoparticles. The average diameter of the tungsten trioxide nanoparticles is 189nm.
[0101] Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution;
[0102] Specifically, the carboxyl-modified PEG, i.e., COOH-PEG-COOH, is dissolved in DMF, and the molecular weight at this time is 1500. 550 mm of EDC and 230 mm of NHS are added as cross-linking agents, and the pH value is adjusted to 4. The solution is stirred at 60°C and 400 r / min until the above substances are completely dissolved in the solution to obtain a 10% concentration of PEG solution. Tungsten trioxide nanoparticle powder is added to the above solution, and the mass proportion of tungsten trioxide nanoparticle powder in the coating solution is 11%. Fatty alcohol polyoxyethylene ether is added as a dispersant, and the amount of fatty alcohol polyoxyethylene ether added is set to 0.5% of the total amount of tungsten trioxide nanoparticle powder. After mixing for 6 hours, 0.3 mmol of ethylenediaminetetraacetic acid is added, and stirred for 6 hours again to obtain a coating solution.
[0103] Step 4: soaking the amino-grafted polyester fiber in the coating solution, and drying the soaked polyester fiber to obtain a photochromic polyester fiber;
[0104] Specifically, the amino-grafted polyester fiber in step 1 is immersed in the coating solution prepared in step 3. The temperature of the coating solution during the immersion process is 65°C, the pH value is 4, and the immersion time is 25 to 40 minutes. The polyester fiber after the immersion is taken out and placed in an oven at 45°C for drying to obtain a photochromic polyester fiber.
[0105] Example 8
[0106] A photochromic polyester fiber and a preparation method thereof, such as Figure 1 As shown, the specific steps include:
[0107] Step 1: Performing a grafting modification operation on polyester fiber using a PET fiber sample to obtain amino-grafted polyester fiber;
[0108] Specifically, in this embodiment, a PET fiber material with a model of ZW120 and a specification of 1.56 dtex×51 mm was selected, and the PET fiber was immersed in an ultrasonic tank containing an ethanol solution, and the PET fiber was cleaned for 25 minutes using ultrasonic technology, and the cleaned PET fiber was dried with argon gas and stored in a dryer at room temperature. The dried PET fiber sample was placed in a spherical glass flask reactor with a capacity of 500 mL. The spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device. When the vacuum degree is increased to 1.5×10 -1mbar, open the valve containing ethylenediamine vapor, i.e., EDA, and inject ethylenediamine vapor into the reactor to perform ionization operation. At this time, the steam flow rate is 80 sccm, and the plasma input power is 200 W. After 15 minutes of plasma treatment, the above process is repeated 3 times, and the treated fiber is washed with ultrapure water. After washing three times, it is dried with argon and stored to obtain amino-grafted polyester fiber. The grafting effect of the amino-grafted polyester fiber is indirectly tested by a water contact angle test method. The contact angle of the amino-grafted polyester fiber is 31°;
[0109] Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method;
[0110] Specifically, the weight ratio between sodium tungstate and sodium sulfate in this embodiment is 4:6. 4g sodium tungstate and 6g sodium sulfate are dissolved in 130mL distilled water, and a 4mol / L HCl solution is added dropwise to the solution while stirring to adjust the pH value of the solution to 1.5. After stirring for 25 minutes, the mixture solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene, and a new product is generated by a hydrothermal reaction. The reaction conditions at this time are to keep warm at 180°C for 48h, and the new product is collected by centrifugation in a high-speed centrifuge. The speed of the centrifuge is 4000 rpm, and the product is washed with distilled water and ethanol to a neutral solution. The neutral solution is dried at a temperature of 60°C to obtain tungsten trioxide nanoparticles. The average diameter of the tungsten trioxide nanoparticles is 174nm.
[0111] Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution;
[0112] Specifically, the carboxyl-modified PEG, i.e., COOH-PEG-COOH, is dissolved in DMF, and the molecular weight at this time is 1000. 700 mm of EDC and 300 mm of NHS are added as cross-linking agents, and the pH value is adjusted to 4. The solution is stirred at 60° C. and 550 r / min until the above substances are completely dissolved in the solution to obtain a PEG solution with a concentration of 12%. Tungsten trioxide nanoparticle powder is added to the above solution, and the mass proportion of tungsten trioxide nanoparticle powder in the coating solution is 9%. Fatty alcohol polyoxyethylene ether is added as a dispersant, and the amount of fatty alcohol polyoxyethylene ether added is set to 0.5% of the total amount of tungsten trioxide nanoparticle powder. After mixing for 6 hours, 0.3 mmol of ethylenediaminetetraacetic acid is added, and the mixture is stirred for 12 hours again to obtain a coating solution.
[0113] Step 4: soaking the amino-grafted polyester fiber in the coating solution, and drying the soaked polyester fiber to obtain a photochromic polyester fiber;
[0114] Specifically, the amino-grafted polyester fiber in step 1 is immersed in the coating solution prepared in step 3. The temperature of the coating solution during the immersion process is 60°C, the pH value is 4, and the immersion time is 35 minutes. The polyester fiber after the immersion is taken out and placed in an oven at 60°C for drying to obtain a photochromic polyester fiber.
[0115] Comparative Example 1
[0116] A photochromic polyester fiber and a preparation method thereof are basically the same as in Example 1, except that the polyester fiber in step 4 is not subjected to grafting modification treatment, other experimental parameters and conditions are the same as in Example 1, the PET fiber is not subjected to grafting modification treatment, and compared with other embodiments, the interface adhesion between the polyester fiber and the coating is poor, the retention rate of the coating decreases after 50 washings, and there are problems such as easy detachment of the coating and poor durability. The specific parameters are shown in Tables 1 and 2.
[0117] Comparative Example 2
[0118] A photochromic polyester fiber and a preparation method thereof are basically the same as in Example 2, except that: in the preparation process of the coating solution in step 3, EDC and NHS are not added, and other experimental parameters and conditions are the same as in Example 2. Although the polyester fiber is treated by grafting modification, the coating solution is not activated, so that an amide bond is not formed between the coating and the modified polyester fiber. Compared with other embodiments, the interfacial bonding effect is weak, there is a problem that the coating is easy to fall off, and the color-changing substance cannot be effectively protected. The specific parameters are shown in Tables 1 and 2.
[0119] Comparative Example 3
[0120] A photochromic polyester fiber and a preparation method thereof are basically the same as in Example 3, except that no ethylenediaminetetraacetic acid (EDTA) is added during the preparation of the coating solution in step 3, and other experimental parameters and conditions are the same as in Example 3. Compared with other embodiments, the color change response speed of the photochromic fiber is worse, and the fading time under natural conditions is shortened, resulting in a reduction in the number of days of effective retention. The specific parameters are shown in Tables 1 and 2.
[0121] Comparative Example 4
[0122] A photochromic polyester fiber and a preparation method thereof are basically the same as those in Example 4, except that no dispersant fatty alcohol polyoxyethylene ether is added during the preparation of the coating solution in step 3, and other experimental parameters and conditions are the same as those in Example 4. Compared with other embodiments, the color-changing substance on the photochromic fiber is unevenly distributed and the color-changing effect is poor. The specific parameters are shown in Tables 1 and 2.
[0123] Specifically, as shown in Table 1 and Table 2, Table 1 shows the performance of the photochromic polyester fiber in different embodiments of the present application, and Table 2 shows the performance of the photochromic polyester fiber in different comparative examples of the prior art. The comparative examples adopt the same configuration as the embodiments by changing a single variable, i.e., whether the polyester fiber is subjected to grafting modification treatment, whether EDC and NHS are added during the preparation of the coating solution, etc., and further conclude that: compared with the preparation process of the photochromic polyester fiber in the prior art, the present application realizes the grafting modification treatment of the polyester fiber by isothermal plasma technology, effectively improves the hydrophilicity of the polyester fiber, and enables the coating solution to form a strong interface bonding effect with the surface of the substrate material. The coating solution adopts carboxyl-modified PEG. Under the action of EDC and NHS, P The carboxyl end (-COOH) of EG is activated and can react with the grafted amino group (-NH2) of polyester fiber to form an amide bond, thereby forming a strong adhesion at the interface between the substrate and the coating. After 50 washes, the retention rate of the coating is still high, which solves the problem of easy detachment of the coating. In addition, EDTA is added to the coating solution system and introduced into the composite material to further effectively enhance the interfacial interaction of the system. Ethylenediaminetetraacetic acid is used as a strong metal ion chelator. The chelator affects the d orbital responsible for light absorption, among which dd transition is the reason for the discoloration of the transition metal coordination compound, which can change the energy level of tungsten oxide in tungsten trioxide nanoparticle powder. Under the repulsion and alienation of oxygen, the photochromic fabric can be effectively preserved for a long time, solving the problem of poor durability of photochromic polyester fiber.
[0124] Table 1
[0125]
[0126] Table 2
[0127]
[0128]
[0129] The above is only a specific implementation of the present application, but the protection scope of the present application is not limited thereto. Any person skilled in the art who is familiar with the present technical field can easily think of changes or substitutions within the technical scope disclosed in the present application, which should be included in the protection scope of the present application. Therefore, the protection scope of the present application should be based on the protection scope of the claims.
Claims
1. A method for preparing a photochromic polyester fiber, characterized in that: The specific steps include: Step 1: Performing a grafting modification operation on polyester fiber using a PET fiber sample to obtain amino-grafted polyester fiber; Step 2: Prepare tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate using a hydrothermal method; Step 3: dissolving the carboxyl-modified PEG in DMF, adding a crosslinking agent and a dispersant, and mixing with tungsten trioxide nanoparticles to prepare a coating solution; Step 4: soak the amino-grafted polyester fiber in the coating solution, and dry the soaked polyester fiber to obtain the photochromic polyester fiber.
2. The method for preparing a photochromic polyester fiber according to claim 1, characterized in that: The grafting modification operation of the polyester fiber in step 1 specifically comprises the following steps: Step 11: immersing the PET fiber in an ultrasonic tank containing an ethanol solution, cleaning the PET fiber using ultrasonic technology, drying the cleaned PET fiber with argon gas, and storing it in a desiccator at room temperature; Step 12: placing the dried PET fiber sample into a spherical glass flask reactor, wherein the spherical glass flask reactor is a vacuum chamber of a low-pressure cold plasma device; Step 13: When the vacuum degree is increased to a specific value, ethylenediamine vapor is injected into the reactor to perform ionization operation, and the above process is repeated several times; Step 14: washing the treated fiber with ultrapure water, drying with argon gas and storing after washing three times to obtain amino-grafted polyester fiber; Step 15: indirectly test the grafting effect of the amino-grafted polyester fiber by a water contact angle test method.
3. The method for preparing a photochromic polyester fiber according to claim 2, characterized in that: The input power of the plasma in step 12 is 150-200 W, and the treatment time of the plasma is 5-15 min.
4. The method for preparing a photochromic polyester fiber according to claim 2, characterized in that: The vacuum degree in step 13 is 1 to 1.5×10 -1 mbar, and the steam flow rate is 70-80 sccm.
5. The method for preparing a photochromic polyester fiber according to claim 1, characterized in that: The step 2 of preparing tungsten trioxide nanoparticles by using sodium tungstate and sodium sulfate specifically comprises the following steps: Step 21: dissolving sodium tungstate and sodium sulfate in distilled water, adding HCl solution dropwise to the solution while stirring, and adjusting the solution to a specific pH after stirring for a period of time, wherein the weight ratio of sodium tungstate and sodium sulfate is 2.5-5:3-6; Step 22: transferring the mixture solution to a stainless steel autoclave lined with polytetrafluoroethylene, and generating a new product by a hydrothermal reaction; Step 23: collect the new product by high-speed centrifugation, wash the product with distilled water and ethanol to a neutral solution, dry the neutral solution at 60°C to obtain tungsten trioxide nanoparticles, the average diameter of the tungsten trioxide nanoparticles is 70 to 200 nm.
6. The method for preparing a photochromic polyester fiber according to claim 5, characterized in that: The reaction conditions of the hydrothermal method in step 22 are: keeping warm at 170-185° C. for 36-48 hours.
7. The method for preparing a photochromic polyester fiber according to claim 1, characterized in that: The step 3 specifically includes the following steps: Step 31: dissolving the carboxyl-modified PEG in DMF, adding a cross-linking agent, and stirring the solution until the above substances are completely dissolved in the solution to obtain a PEG solution with a concentration of 10 to 15%; Step 32: Add tungsten trioxide nanoparticle powder to the above solution, then add a dispersant, mix for 6 hours, then add 0.3-0.6 mmol of ethylenediaminetetraacetic acid, stir again for 6-12 hours to obtain a coating solution.
8. The method for preparing a photochromic polyester fiber according to claim 7, characterized in that: The cross-linking agents in step 31 are EDC and NHS, the concentration range of EDC is 500-800 mM, and the concentration range of NHS is 150-300 mM; The mass proportion of the tungsten trioxide nanoparticle powder in the coating solution in step 32 is 7-14%, the dispersant is fatty alcohol polyoxyethylene ether, and the amount of the fatty alcohol polyoxyethylene ether added is 0.5-1% of the total amount of the tungsten trioxide nanoparticle powder.
9. The method for preparing a photochromic polyester fiber according to claim 1, characterized in that: The step 4 specifically includes the following steps: soaking the amino-grafted polyester fiber in step 1 in the coating solution prepared in step 3, maintaining the temperature of the coating solution between 60 and 65°C, maintaining the pH value between 4 and 6, and soaking for 25 to 40 minutes, and then drying the polyester fiber after soaking to obtain photochromic polyester fiber.
10. A photochromic polyester fiber, characterized in that: The product is processed by the method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Polyamide / polyester photosensitive color-changing composite fiber
CN105603576A
Photochromic polyester, polyester fiber and preparation method
CN115594855A
Preparation method of photochromic fiber
CN118223287A